An Optimal-Pruned Extreme Learning Machine based modelling of surface roughness - Janahiraman T.V.; Ahmad N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Computer control systems; Cutting tools; Forecasting; Knowledge acquisition; Learning systems; Neural networks; Numerical methods; Surface properties; Turning; Back propagation neural networks; Computer numerical control; Cutting operations; Efficient predictions; Extreme learning machine; Response surface method; Response surface methodology; Surface roughness model; Surface roughness